2014
DOI: 10.1007/s11192-014-1439-8
|View full text |Cite
|
Sign up to set email alerts
|

How have the Eastern European countries of the former Warsaw Pact developed since 1990? A bibliometric study

Abstract: Did the demise of the Soviet Union in 1991 influence the scientific performance of the researchers in Eastern European countries? Did this historical event affect international collaboration by researchers from the Eastern European countries with those of Western countries? Did it also change international collaboration among researchers from the Eastern European countries? Trying to answer these questions, this study aims to shed light on international collaboration by researchers from the Eastern European co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 23 publications
5
53
1
5
Order By: Relevance
“…Thus, Karamourzov (2012) analysed development trends in the Commonwealth of Independent States and demonstrated the large, and in some cases, near catastrophic, reductions in scientific activity that have taken place. Kozak et al (2014) showed that the break-up of the Block did not result in significant increase in publication counts or in academic collaborations with international researchers. Radosevic and Yoruk (2014) compared the science and social science capabilities of the countries of Central and Eastern Europe with those of the longestablished members of the European Union.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, Karamourzov (2012) analysed development trends in the Commonwealth of Independent States and demonstrated the large, and in some cases, near catastrophic, reductions in scientific activity that have taken place. Kozak et al (2014) showed that the break-up of the Block did not result in significant increase in publication counts or in academic collaborations with international researchers. Radosevic and Yoruk (2014) compared the science and social science capabilities of the countries of Central and Eastern Europe with those of the longestablished members of the European Union.…”
Section: Introductionmentioning
confidence: 98%
“…Hence, citation analysis helps researchers to obtain a preliminary idea about the articles and research that has an impact in a particular field of interest and it deals with the examination of the documents cited by scholarly works [29,30]. In addition, there are various bibliometric studies has been evaluated based on different metrics and applications such as forecasting emerging technologies by using bibliometric and patent analysis [31], multiple regression analysis for Japanese patent case [32], medical innovation using medical subject headings [33], based on region or countries [34][35][36], number of authors [37,38] and a bibliometric analysis based on number publications and cited references [39].…”
Section: Introductionmentioning
confidence: 99%
“…While import substitution may result in short-term improvements of technological capabilities, insufficient access to the often tacit complementary knowledge required to create cutting-edge products is likely to act as a drain on innovative performance in the long run. Recent trends provide cause for concern, with MNEs considering divestment (Jost, 2015) and Russian researchers' international collaborations trending downward (Kozak et al, 2015). Our analysis strongly suggests that it would not be major agglomerations like Moscow but remote regions whose performance would be most severely affected by reduced integration in global networks.…”
Section: Resultsmentioning
confidence: 86%